Peran Guru BK Dalam Menangani Prilaku Membolos Siswa Di MTs Nu Raudlatus Shibyan - M. Dafiq Dhiya'ul Haq (IAIN Kudus, 2019)
The Role Of The Guidance and Counseling Teacher In Handling The Private Vocational School Of Students At MTs Nu Raudlatus Shibyan. Truancy is bad behavior by students, such as not entering school without permission, not entering certain class hours, returning home when school hours have not finished. This study aims to determine what causes students to practice truancy and the consequences of truant behavior at MTs NU Raudlatus Shibyan. As is well known, the impact of truancy is experiencing failure in learning. In this research, the research method used is descriptive qualitative method. From the research conducted, it is found that truancy behavior is influenced by internal and external factors, such as lack of motivation and interest in learning, juvenile delinquency, influenced by friends who like truant, dislike certain lessons and teachers. The result of truancy is that they often receive calls from counseling teachers, and miss lessons, resulting in lower grades, or the most fatal is being expelled from school.Keywords: Truancy Behavior, Internal Factors, External Factors